Processing and Preparation Method for High-Quality Opto-Electronic Perovskite Film - Chen, Zheng; He, Ping; Wu, Dan; Chen, Chen; Mujahid, Muhammad; Li, Ye; Duan, Yu (Frontiers in Materials, 2021)
The key to improve the energy conversion efficiency of perovskite solar cellslies in the optimizing of the film morphology. The optical and electrical properties of the perovskite film, such as light absorption, carrier diffusion length, and charge transport, are all directly affected by the film morphology. Therefore, this review starts from the perovskite solar cells structure, and it summarizes the state-of-art perovskite film fabrication technologies and the caused film morphology to the performance perovskite solar cells. The spin coating method has an enormous waste of materials and only a small area of the device that can be utilized. It is difficult to be used in commercial manufacturing. However, due to the high efficiency of this preparation method, it is irreplaceable in the initial research and development of perovskite materials, this method will be popular for a long time in the laboratory. Chemical vapor deposition and thermal vapor deposition have high technical requirements, good repeatability of processing and manufacturing, and large-scale production can be realized. It may be the first technology to admit industrial application; the scratch coating method and slot-die have significant technical aspects. The similarity of the roll-to-roll manufacturing technology is also an efficient preparation method. Still, to achieve high-efficiency devices, it is necessary to consider the thickness control of each functional layers, and to find or prepare perovskite paste. Finally, we summarized the various fabrication process and the prospect of the commercialization of perovskite solar cells. We prospect that to achieve the commercialization of perovskite solar cells, the existing fabrication technologies should be optimized and more efforts should be conducted.